Community-Based Hepatitis B Education Program For Healthcare Workers And Posyandu Cadres In Gondanglegi District, Malang Regency - Supriono, Supriono; Wibowo, Bogi Pratomo; Mustika, Syifa; Fachrureza, Mochamad; Arti, Andani Putri Budi; Fanani, Reza; Setiawan, Maruli (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2026)
Hepatitis B remains a significant public health concern due to its high transmissibility and potential for long-term complications, including chronic liver disease and cirrhosis. Strengthening the knowledge of healthcare workers and Posyandu cadres is essential to enhancing community-based prevention and early detection efforts. This community service program aimed to improve hepatitis B knowledge among healthcare workers and Posyandu cadres in Gondanglegi District, Malang Regency. A quasi-experimental pre-test–post-test design was used, and the educational intervention included a presentation, a booklet, and an educational video delivered by a gastroenterohepatology consultant. Data were analyzed using paired t-test. A total of 87 participants were involved, comprising 24 healthcare workers and 63 cadres. The evaluation showed a significant improvement in knowledge across both groups. The cadres’ mean score increased from 59.3 to 72.3, while the healthcare workers’ mean score increased from 61.8 to 84.2, with both groups demonstrating statistical significance (p < 0.001). Participants also showed strong engagement during discussions, particularly related to transmission pathways, risks in pregnancy, screening, and vaccination. These findings indicate that multimodal educational interventions are effective in improving hepatitis B literacy among key community health actors. Enhanced knowledge is expected to support early detection, strengthen community education, and contribute to national hepatitis elimination efforts. Overall, this program demonstrated a meaningful impact on participant competence and highlights the importance of integrating similar educational activities into routine community health programs and utilizing existing educational media for continuous reinforcement of hepatitis B prevention at the community level.